2014
DOI: 10.4028/www.scientific.net/amm.607.153
|View full text |Cite
|
Sign up to set email alerts
|

Improving Rate of Penetration for PDC Drill Bit Using Reverse Engineering

Abstract: In petroleum industry, drilling is one of the most important aspects due to its economics. Reduction in drilling time is desired to minimize operations cost. This work focus on Polycrystalline Diamond Compact (PDC) drill bit which is categorized as a fixed cutter drilling bit. Problem such as wear and tear of PDC cutter are some of the main factors in drilling process failure affecting the rate of penetration (RoP). Thus, an intensive study in drill bit design could potentially save costs if the drill bit effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…where V m is mechanical drilling speed, m/s. Analysis of formula (10) shows that the first terms in brack ets depend on the position of the cutting element on the blade, i. e. on its radius of rotation R i , defined by the formula (9). The second term does not depend on R i .…”
Section: B K =mentioning
confidence: 99%
See 1 more Smart Citation
“…where V m is mechanical drilling speed, m/s. Analysis of formula (10) shows that the first terms in brack ets depend on the position of the cutting element on the blade, i. e. on its radius of rotation R i , defined by the formula (9). The second term does not depend on R i .…”
Section: B K =mentioning
confidence: 99%
“…In [10], the influence of various factors on the mechanical drilling rate was analyzed. In particular, it was found that with a decrease in the inclination angle of the cutting plate, as well as with a decrease in its lateral angle of the installation, the fracture efficiency increases.…”
mentioning
confidence: 99%